2013
DOI: 10.1002/ibd.23000
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Targeted MHC-II Transgenic Mice Demonstrate the Role of Dendritic Cells in Bacterial-driven Colitis

Abstract: Background Inflammatory bowel disease (IBD) pathogenesis involves an inadequately controlled immune reaction to intestinal microbiota and CD4+ T cells, dependent upon MHC class II (MHC-II) processing and presentation by antigen presenting cells (APC), play important roles The role of professional APC (macrophages and dendritic cells (DC)) and nonprofessional APC (intestinal epithelial cells (IEC)) in microbial driven intestinal inflammation remains controversial. Methods We generated transgenic animals on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Maggio-Price et al induced colonic inflammation in RAG2 −/− mice exclusively expressing MHC class II either on IECs or DCs. Animals with MHC class II + DCs developed severe colitis, whereas mice with MHC class II on IECs developed only mild inflammation ( 125 ). Additionally, mice lacking MHC class II on DCs appeared to develop intestinal inflammation due to lack of proper CD4 + T cell-mediated adaptive immune responses to commensal bacteria, as gnotobiotic mice under the same conditions did not develop inflammation ( 126 ).…”
Section: Potential Role Of Ecs In Antigen Presentationmentioning
confidence: 99%
“…Maggio-Price et al induced colonic inflammation in RAG2 −/− mice exclusively expressing MHC class II either on IECs or DCs. Animals with MHC class II + DCs developed severe colitis, whereas mice with MHC class II on IECs developed only mild inflammation ( 125 ). Additionally, mice lacking MHC class II on DCs appeared to develop intestinal inflammation due to lack of proper CD4 + T cell-mediated adaptive immune responses to commensal bacteria, as gnotobiotic mice under the same conditions did not develop inflammation ( 126 ).…”
Section: Potential Role Of Ecs In Antigen Presentationmentioning
confidence: 99%
“…[5][6][7] A monolayer of IEC not only forms a physical barrier separating host from luminal environment, but also interacts with other immune cells, such as T cells and dendritic cells. [8][9][10] An impaired epithelial barrier provides the opportunity for gut microbiota invasion and causes intestinal inflammation. However, it is still not completely clear how intestinal epithelial barrier is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…However, regulatory T cells were also induced in the respective mouse models in response to epithelial MHC class II presentation and may have contributed to the control of intestinal inflammation ( Westendorf et al, 2006( Westendorf et al, , 2009. The concept of regulatory functions of IEC-dependent MHC class II restricted Ag presentation in vivo was further supported by two studies, which demonstrated that epithelial MHC class II expression in mice does not contribute to infection-induced colitis, but instead elicits regulatory effects associated with protection from intestinal inflammation (Maggio-Price et al, 2013;Thelemann et al, 2014). Thus, intestinal epithelial MHC class II restricted Ag presentation can initiate both proinflammatory as well as regulatory T cell responses.…”
Section: Peptide Antigen Presentation By Intestinal Epithelial Cellsmentioning
confidence: 91%